2022
DOI: 10.3390/life12050715
|View full text |Cite
|
Sign up to set email alerts
|

Preservative Contact Hypersensitivity among Adult Atopic Dermatitis Patients

Abstract: Atopic dermatitis (AD) is a chronic inflammatory disease characterised by an impaired skin barrier. The prolonged use of topical preparations containing medications, emollients, fragrances and preservatives may increase the risk of contact hypersensitivity (CHS). In the Allergy Outpatient Unit of the Department of Dermatology, Venereology and Dermatooncology of Semmelweis University, 5790 adult patients were patch tested between 2007–2021 with the European Environmental Baseline Series according to internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…In our study, a total of 24 positive reactions to methylisothiazolinone (MI), Kathon CG®, methyldibromo glutaronitrile (MDBNH), formaldehyde, and quaternium-15 or 12.7% of contact hypersensitivity in atopics were found. According to Németh et al (2022), in 639 patients with AD and ACD, contact sensitization to preservatives was 10.6%, with the most common concomitant combination being Kathon CG® + MI [21]. As early as 1990, A. C. de Groot reported a high incidence of positive reactions to nickel (18.8%), cobalt (6%), Kathon CG (4.8%), and Balsam of Peru (3.6%) in 214 atopic patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, a total of 24 positive reactions to methylisothiazolinone (MI), Kathon CG®, methyldibromo glutaronitrile (MDBNH), formaldehyde, and quaternium-15 or 12.7% of contact hypersensitivity in atopics were found. According to Németh et al (2022), in 639 patients with AD and ACD, contact sensitization to preservatives was 10.6%, with the most common concomitant combination being Kathon CG® + MI [21]. As early as 1990, A. C. de Groot reported a high incidence of positive reactions to nickel (18.8%), cobalt (6%), Kathon CG (4.8%), and Balsam of Peru (3.6%) in 214 atopic patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…In individuals with sensitive skin, exposure to rapid changes in physical and chemical conditions or variations in environmental temperature can lead to the rapid expansion of skin microvessels and increased blood fow, resulting in fushing of the skin [17]. In addition, the accelerated blood fow enhances the absorption of external irritants, increasing the likelihood of uncomfortable sensations such as itching, burning, or tingling [18]. Studies have demonstrated that the prevalence of sensitive skin is approximately 36.1% in China and around 50% in Japan, Europe, and the United States [19].…”
Section: Discussionmentioning
confidence: 99%
“…Rendszerint már csecsemőkorban megjelennek a bőrtünetek, ami az "atópiás menetelés" első lépése lehet, később allergiás rhinitis (szénanátha), majd asthma bronchiale követheti (Kárpáti, Gyulai, Kemény, Remenyik, & Sárdy, 2019). Az AD gyakran társul -elsősorban a kozmetikai szerekben található tartósítószerek iránti -kontakt hiperszenziti vitással is (Németh, Temesvári, Holló, & Pónyai, 2022). A gyakran nedvedző és pörkösödő tünetek kezdetben az orcákon, a homlokon és a hajas fejbőrön láthatóak, ezt követően a törzsre és a végtagok feszítő felszíneire terjednek ki, típusosan a pelenka alatti terület megkímélt.…”
Section: Az Atópiás Dermatitis Jellemzőiunclassified